Roskilde 6 – et langskib fra Norge – Proveniens og alder - Bonde, Niels; Stylegar, Frans-Arne (Kuml, 2011)
Roskilde 6 – a long-ship from Viken Provenance and date During works on construction of the Museum Island in Roskilde in 1996-97, ten historical shipwrecks were discovered, all built primarily of oak. Preliminary dendrochronological investigations revealed that these represented ships ranging in date from the beginning of the 11th century to the beginning of the 15th century AD, i.e. a period during which Roskilde was one of the most important towns in the Danish Kingdom. One of the wrecks, termed ‘Roskilde 6’, stands out from the rest. It is the oldest of the ten vessels and also the largest Viking ship found to date. It belongs to the group of the Late Viking Age long, narrow warships and would have had a crew of more than a hundred. Seen in the light of documentary sources there is reason to believe that this was a warship which belonged to a person of very high rank. The dendrochronological dates fix the time of the ship’s construction at AD 1025-26 and the investigations also revealed that the ship was built using oak trees that grew in the areas around Oslo Fjord, probably in Vestfold. The ship was probably actually built in Vestfold. It was constructed at a time when hostilities culminated between Norwegian Olaf Haraldsson (the Holy), who imposed royal power on areas of Danish interest around Oslo Fjord, and the Danish king, Canute the Great, who tempted to hold together his so-called North Sea Empire. ‘Roskilde 6’ was very probably involved in the battle at the mouth of the river Helgeå, on the east coast of Scania, which took place in AD 1026. According to documentary sources, the battle between the army of Olaf Haraldsson and the Swedish king Anund Jacob, on one side, and Canute the Great’s army, on the other, ended more or less undecided. Whether this is correct is impossible to ascertain. One thing is, however, certain: the battle marked the beginning of Olaf’s decline. We cannot know on which side ‘Roskilde 6’ took part, but the vessel continued in use for a further c. 20-30 years before it ended up on the shore meadows below Roskilde. Niels Bonde Nationalmuseet Frans-Arne Stylegar Vest-Agder Fylkeskommune Kristiansand